Democracy, elections, and constitutionalism in Africa - Fombad, Charles Manga; Steytler, N. C.; Stellenbosch Annual Seminar on Constitutionalism in Africa 2018 : Stellenbosch, South Africa) (Oxford : Oxford University Press, 2021)
The third wave of democracy that reached African shores at the end of the Cold War brought with it a dramatic decline from 1990 onwards in dictatorships, military regimes, one-party governments, and presidents for life. Multiparty democracy was at the core of the constitutional revolutions that swept through most of Africa in those watershed years. However, that wave is either losing momentum or receding - or being reversed in its entirety. This volume examines democracy and elections in Africa.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 15, 2021).
Keywords: Democracy -- Africa; Elections -- Africa; Africa -- Politics and government -- 1960-; Constitutional law -- Africa